An investigation into the intra-sample variation in the color of cotton using image analysis. Issue 2 (January 2014) - Cui, Xiaoliang; Cai, Yiyun; Rodgers, James; Martin, Vikki; Watson, Mike
The colorimeter method is widely used to identify the color and grade of a cotton sample, but this method does not give information about the variation of color within the sample. We have conducted an investigation using an image analysis method to study the intra-sample distribution and variation in cotton color. High-resolution color images of cotton samples were obtained using a color scanner. For each image the Rd and + b values of the image and specific sub-areas within it were computed to analyze the color distribution. Intra- and inter-sample variations in Rd and + b values and color grade were compared with those obtained by the HVI system. The results show that for the same cotton substrate, although the variations among the color grades of different samples (replicates) may be very small, intra-sample color variations are evident, the colors of the sub-areas being distributed over a range of areas of the cotton color chart. In other words, cotton samples of the same overall color grade may exhibit different intra-sample color variations and distribution. A description of the intra-sample color variations and distributions obtainable using an image analysis method may allow a more comprehensive evaluation of color characteristics on cotton.